An RGB to RGBG conversion algorithm for AMOLED panel - Huang, Chengqiang; Zhang, Qi; Wang, Hui; Feng, Songlin (Journal of the Society for Information Display, 2017)
In this paper, an RGB‐to‐RGBG conversion algorithm based on the weighting factor (WF) has been proposed. The gray level of each RGBG sub‐pixel is represented by the weighted sum of the original gray levels. The weighting factors are adaptively calculated by minimizing the square error. Furthermore, the color fringing artifact is significantly improved by using this method. Peak signal‐to‐noise ratio of U component and peak signal‐to‐noise ratio of V component of the image processed by WF is larger than that processed by direct assignment and FRB. The mean square error of the image processed by the WF is 14% and 53% smaller than that of image processed by direct assignment and FRB, respectively. The proposed algorithm has been implemented on a field‐programmable gate array, and the displayed image has good visual effect. In this paper, an RGB‐to‐RGBG conversion algorithm based on weighting factor (WF) has been proposed. Peak signal‐to‐noise ratio of U component and peak signal‐to‐noise ratio of V component of image processed by WF is larger than that processed by direct assignment and FRB. Mean square error of image processed by the WF is 14% and 53% smaller than that of image processed by the direct assignment and FRB, respectively.